2016
DOI: 10.1007/s10792-016-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser cyclophotocoagulation paves way to a safer trabeculectomy in eyes with medically uncontrollable intraocular pressure

Abstract: High intraocular pressure (IOP) not responding to systemic and topical anti-glaucoma medications renders the eye at risk for both intra- and post-operative complications of glaucoma filtration surgery. Laser cyclophotocoagulation is able to lower IOP in such refractory glaucoma eyes and may make the surgical event safer. This study assessed diode laser cyclophotocoagulation (DLCP) when used as a temporary measure for lowering IOP prior to performing trabeculectomy. This study is a  retrospective analysis of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although CPC has been studied in the early stages of glaucoma (Egbert et al 2001; Kramp et al 2002; Singh et al 2017b; Abdull et al 2018), its complications remain common enough to limit its use to the treatment of glaucoma refractory to conventional surgical treatments (Michelessi et al 2018; Hasan et al 2019; Paul et al 2019) (Table 3). Moreover, the inflammatory (mostly CD4 T‐cell lymphocytic infiltrates) and fibrotic histological conjunctival lesions induced by the procedure are likely to impair future filtration blebs (Tan et al 2019).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…Although CPC has been studied in the early stages of glaucoma (Egbert et al 2001; Kramp et al 2002; Singh et al 2017b; Abdull et al 2018), its complications remain common enough to limit its use to the treatment of glaucoma refractory to conventional surgical treatments (Michelessi et al 2018; Hasan et al 2019; Paul et al 2019) (Table 3). Moreover, the inflammatory (mostly CD4 T‐cell lymphocytic infiltrates) and fibrotic histological conjunctival lesions induced by the procedure are likely to impair future filtration blebs (Tan et al 2019).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…These findings were also corroborated by Kuchar et al [13] in advanced glaucoma patients, who reported a mean IOP drop of 40.1% and a mean follo time of 60 days with minimal complications. Singh et al [14] studied its use as a temporary measure to lower IOP before trabeculectomy in refractory glaucoma and reported 51% reduction in IOP by one week. Our study population was however made up of only POAG patients.…”
Section: Comparison Of Mean Change In Visual Acuity In Logmar Unitsmentioning
confidence: 99%
“…Consequently, cyclo-ablative laser procedures have traditionally been reserved for eyes with poor visual potential, or as a last resort after multiple glaucoma filtration surgeries have failed [ 1 ]. Although there is some, albeit limited, evidence to suggest the safety and efficacy of transscleral diode laser cyclophotocoagulation for temporary intraocular pressure (IOP) control for medically refractory glaucoma prior to trabeculectomy surgery [ 2 ], general consensus has been to avoid cyclo-destructive procedures prior to a trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%